Perencanaan Ulang Sistem Drainase Menggunakan SWMM 5.2 di Kecamatan Bojongloa Kidul, Kota Bandung - Zeihan Niswanurrahim (Jurnal Serambi Engineering, 2026)
Bojongloa Kidul District is a low-lying area crossed by a river, making it prone to flooding. Flooding occurs due to rainwater overflowing drainage channels that cannot be accommodated by the Citepus River. The purpose of this plan is to redesign the drainage system in Bojongloa Kidul Subdistrict and provide solutions and recommendations for flooding and waterlogging problems using the SWMM 5.2 application. The planning was carried out in Cibaduyut Kidul and Cibaduyut Wetan villages as priority areas for flood management based on the scoring results of the Minister of Public Works and Public Housing Regulation No. 12 of 2014 concerning The Implementation Of Urban Drainage Infrastructure. Based on the evaluation results, there are problematic channel segments on Jalan Terusan Cibaduyut -Cibaduyut Tunnel, namely flooding at junctions J19, J23, J29, and J30 which are marked in red in the SWMM 5.2 simulation, thus affecting the entire route to outlet 2, outlet 3, outlet 4, outlet 6, and outfall 2, with a runoff flow rate of 21.73 m³/s. Channel dimension improvements were carried out by increasing the channel depth to ensure sufficient capacity.